Effects of coping designs on fracture modes in zirconia crowns: Progressive load test. Issue 6 (1st May 2016) - Ha, Seung-Ryong; Kim, Sung-Hun; Lee, Jai-Bong; Han, Jung-Suk; Yeo, In-Sung
Abstract: This study was designed to evaluate the effects of different coping designs on the fracture modes of posterior zirconia crowns. One hundred mandibular molar copings of ten different designs were fabricated from 3Y-TZP. All ten different groups ( n =10) had 1 mm wide shoulder, but they had varying heights of 1 mm, 2 mm, or 3 mm on the buccal, lingual and proximal sides. After being sintered and veneered, the zirconia crowns on titanium abutments were stored in distilled water at 37 °C for 24 h. Then they were loaded into a universal testing machine. The veneer fracture load and bulk fracture load values were measured. Moreover, the fracture surfaces were examined with a scanning electron microscope. One-way analysis of variance and the Scheffé posthoc test were carried out for statistical analyses ( α =.05). Higher shoulders on the buccal, lingual and proximal sides resulted in higher fracture load values. As the heights of the shoulders increased, the occurrence of chipping decreased. Additionally, the bulk fractures on the buccal surfaces increased in the crowns with higher shoulders. We concluded that the shoulder coping design plays a critical role in the survival of posterior zirconia restorations by reducing veneering porcelain fractures.